The effect of in-situ decompression on ulnar nerve stability: a cadaveric study. (September 2017) - Butler, B.; Peelman, J.; Zhang, L.-Q.; Kwasny, M.; Nagle, D.
Ten fresh frozen right cadaver arms were placed in a motorized jig and an in-situ ulnar nerve decompression was performed in 5 mm increments distally to the flexor carpi ulnaris (FCU) aponeurosis then proximally to the intermuscular septum. The elbows were ranged 0–135° after each incremental decompression and the ulnar nerve to medial epicodyle distance was measured to assess for nerve translation/subluxation compared with baseline (prerelease) values. None of the specimens had ulnar nerve subluxation (defined as anterior translation past the medial epicondyle) even after full decompression. Furthermore, there were no statistically significant ulnar nerve translations (defined as any difference in distance from ulnar nerve to medial epicondyle before and after each decompression) for any flexion angle or extent of decompression. This study provides biomechanical evidence that in situ ulnar nerve decompression from the FCU aponeurosis to the intermuscular septum does not result in significant ulnar nerve translation or subluxation.